Late Cretaceous Foraminiferal Biozonation in Selected Wells of Nasiriya Oilfield, Southern Iraq - Hussain, Salah; Methaq Y. Tulub (ASJ - Academic Science Journal, 2025)
Mishrif Formation is considered as very important Cretaceous reserves, previously its petrophysical characterization and diagenetic operations are the most common studies by many authors. This study focused on the biozonation and age determination of the formation in three selected subsurface sections of Nasiriya Oilfield which situated in Thi Qar Governorate, South of Iraq. The results show that in these two sections, only on benthic foraminifera biozone was discriminated which is: Nezzazata simplex-Nezzazata conica Interval Biozone, dated as Middle-Late Cenomanian (early Late Cretaceous), which indicates the highest occurrence of two successive taxa. The thickness of this biozone is 42 meter in well NS-7 and the lithology is brown-light brown, slightly hard, fine - medium crystalline limestone, and in parts compact white, moderately hard, fine crystalline limestone, and in well NS-8 the lithology is, brown to light brown, slightly hard, medium crystalline, porous, vuggy limestone, the thickness is 36.9 meter. However, NS-4 is fossil baren.